PENGARUH PROBLEM BASED LEARNING (PBL) DALAM PEMBENTUKAN KARAKTER KEPEMIMPINAN SISWA SDN 2 BAJUGAN: Kuantitatif Quasi Experimental - Ernawati; Mustakim; Nasriani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the influence of the implementation of the based learning (PBL) program on the formation of student leadership character at SDN 2 Bajugan. The type of research in this study is quantitative correlation with the quasi experimental design of the pretest-posttest type which was carried out on students of SDN 2 Bajugan with a total population of 255 students. The research sample consisted of two classes, namely class 5A with 23 students and class 5B with 22 students selected using purposive sampling. Data collection is carried out through observation and tests. Data analysis using SPSS 25 software. The results showed the significance of the based learning (PBL) program in the Mann-Whitney U Test (0.033) > 0.050. The results of the character formation of SDN 2 Bajugan students there are differences between classes 5A and 5B where the results in the class implementing the program based learning (PBL) model are 51,22 for class 5A, while class 5B is 39,52. Thus, the implementation of the based learning (PBL) program as a whole has a significant effect in helping the formation of leadership character in SDN 2 Bajugan students.